2012
DOI: 10.2174/157340311799960636
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of Molecularly Targeted Agents

Abstract: Cardiac toxicity of molecularly targeted cancer agents is increasingly recognized as a significant side effect of chemotherapy. These new potent therapies may not only affect the survival of cancer cells, but have the potential to adversely impact normal cardiac and vascular function. Unraveling the mechanisms by which these therapies affect the heart and vasculature is crucial for improving drug design and finding alternative therapies to protect patients predisposed to cardiovascular disease. In this review,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 144 publications
0
16
1
Order By: Relevance
“…Although VEGFIs have been associated with thrombotic and hemorrhagic side effects, 44 , 45 the prothrombotic effects appear to predominate. VEGFIs are associated with an absolute increase in risk of arterial and venous thrombosis and thromboembolism of 1.5%-4%.…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…Although VEGFIs have been associated with thrombotic and hemorrhagic side effects, 44 , 45 the prothrombotic effects appear to predominate. VEGFIs are associated with an absolute increase in risk of arterial and venous thrombosis and thromboembolism of 1.5%-4%.…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…According to the latest reports, approximately 76 targeted anticancer drugs received approval from the US FDA from 2001 to May 2017; these drugs include small molecule kinase inhibitors, other types of agents (e.g., proteasome and histone deacetylases targeting inhibitors) (Table ), and therapeutic monoclonal antibodies (Tables and ). The clinical patterns of toxicity associated with some of these agents have been addressed or discussed in detail in other reviews . Many of the approved drugs are protein kinase inhibitors (PKIs), typically protein tyrosine kinase inhibitors (TKIs) .…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%
“…In addition, targeting the ubiquitin‐proteasome pathway is an emerging concept in cancer therapy based on the hypothesis that many proteins in the proteasome are implicated in the regulation of important processes of carcinogenesis and cancer cell survival . Several proteasome‐targeting inhibitors (e.g., bortezomib, carfilzomib) have been introduced in the clinic. A retrospective analysis of 3954 patients in phase 2/3 trials of bortezomib for the treatment of multiple myeloma reported that bortezomib‐based treatment was associated with a low incidence of cardiac events .…”
Section: Fda‐approved Mtts For Oncologymentioning
confidence: 99%
See 2 more Smart Citations